A comprehensive analysis of AlN spacer and AlGaN n-doping effects on the 2DEG resistance in AlGaN/AlN/GaN heterostructures. (August 2022) - Piotrowicz, C.; Mohamad, B.; Rrustemi, B.; Malbert, N.; Jaud, M.A.; Vandendaele, W.; Charles, M.; Gwoziecki, R.
Highlights: AlN polarization is attenuated for very thin layers. n-Doped AlGaN improves the on state resistance because it creates an electron channel in AlGaN. Negligible impact of AlGaN n-doping on the 2DEG density. Abstract: In this paper, several epitaxial variations influencing the two-dimensional electron gas (2DEG) in AlGaN/AlN/GaN heterostructures are investigated. The effects of an n-doped AlGaN barrier and of the AlN spacer thickness are studied by examining the sheet electron density (ns ) and the mobility (µs ) of the 2DEG using ID (VG ) and C(VG ) measurements, and 1D Schrödinger-Poisson (1DSP) simulations. Specifically, the correlations between the resistance, µs, ns and the polarization interface charges (σ) are studied. Besides the well-reported benefits of the AlN spacer on ns, we show that a thicker AlN spacer leads to larger ns due to the enhancement of the AlN polarization. In addition, we prove experimentally that an n-doped AlGaN barrier does not significantly improve the 2DEG density but leads to the formation of a second channel in the AlGaN barrier for negative gate voltage (VG ≤ 0 V), driving the overall improvement of the resistance.